Impacts of QX disease on the population and habitat structure of Sydney rock oysters, Saccostrea glomerata (Gould), in the Hawkesbury River, NSW, Australia - Summerhayes, SA (2008)
University of Technology, Sydney. Faculty of Science. Oysters are ubiquitous and conspicuous components of estuarine systems. They play pivotal structural and functional roles, providing an array of ecosystem services of commercial, biological and social value. In the Hawkesbury River estuary, NSW, Australia, two oyster species co-occur, the endemic Sydney rock oyster, Saccostrea glomerata, and the non-native Pacific oyster, Crassostrea gigas, a noxious species occupying a small proportion of the estuary's oyster population. In 2004, Queensland Unknown (QX) disease caused by the protozoan parasite, Martelia sydneyi, led to catastrophic mortality of cultivated S. glomerata. Industry turned to QX resistant strains, which have produced mixed success, and triploid C. gigas which, although successful, produce small numbers of fecund diploid offspring which can release larvae, increasing pressure upon wild natives. If QX similarly impacts wild S. glomerata, both death and subsequent shell degradation could alter the facilitation of biodiversity and assist invasion of faster growing Pacific oysters. To identify whether wild S. glomerata have experienced similar mortality to aquaculture oysters and to assess changes in invasive C. gigas abundance, this research sampled oyster cover, species composition, abundance, size and condition in two key habitats: rocky shore and mangrove, along-estuary. Sampling revealed sizeable populations of live natives dominated by individuals sufficiently large to have survived QX seasons. Abundance differed between habitats but% mortality: size and condition did not, although trends of increasing % mortality and size with distance up-estuary were evident. C. gigas abundance was similar to previous estimates. To evaluate effects of oyster habitat degradation on biodiversity, using the natural gradient of % mortality, oysters and epifauna occupying 100% oyster cover were identified and enumerated at sites along-estuary. Epifaunal community structure differed among sites, following an along-estuary gradient correlated with live oyster abundance. To separate effects of mortality and shell degradation from salinity, habitat structural components (live oysters, dead and degraded shell) were manipulated with comparisons against sandstone oyster mimics. Treatments containing a component of half shells (greater interstitial spaces and surface area) supported greatest epibiota abundance. Matrices comprised solely of live oysters supported fewest species and numbers of organisms, perhaps due to filter feeding depleting resources. Oyster analogues supported similar diversity to natural assemblages, but could not replicate community composition. This study assists in understanding the nature and magnitude of impacts on wild oyster populations subsequent to a major aquaculture disease event. It also illustrates the effects of oyster mortality upon associated biodiversity, exemplifying the need to maintain live oyster populations to preserve unique biotic assemblages. The biological and ecological functions of oysters render this information crucial to the preservation of the extensive ecosystem services provided by estuaries and oysters.